The Hox gene Abd-B controls stem cell niche function in the Drosophila testis - Papagiannouli, Fani; Schardt, Lisa; Grajcarek, Janin; Ha, Nati; Lohmann, Ingrid (Developmental cell, 2014)
Proper niche architecture is critical for stem cell function, yet only few upstream regulators are known. Here, we report that the Hox transcription factor Abdominal-B (Abd-B), active in premeiotic spermatocytes of Drosophila testes, is essential for positioning the niche to the testis anterior by regulating integrin in neighboring somatic cyst cells. Abd-B also non-cell-autonomously controls critical features within the niche, including centrosome orientation and division rates of germline stem cells. By using genome-wide binding studies, we find that Abd-B mediates its effects on integrin localization by directly controlling at multiple levels the signaling activity of the Sev ligand Boss via its direct targets src42A and sec63, two genes involved in protein trafficking and recycling. Our data show that Abd-B, through local signaling between adjucent cell types, provides positional cues for integrin localization, which is critical for placement of the distant stem cell niche and stem cell activity.
Gesehen am 16.10.2020